Decreased survival of subjects with elevated liver function tests during a 28‐year follow‐up - Söderberg, Cecilia; Stål, Per; Askling, Johan; Glaumann, Hans; Lindberg, Greger; Marmur, Joel; Hultcrantz, Rolf (Hepatology (Baltimore, Md.), 2010)
The long‐term survival of subjects with nonalcoholic fatty liver disease (NAFLD) in comparison with both individuals with elevated transaminases attributable to other causes and the general poulation is poorly characterized. This study was undertaken to determine the frequency of NAFLD in a cohort of subjects who underwent liver biopsy from 1980 to 1984 because of elevated liver enzymes, and to assess mortality among subjects with NAFLD in comparison with the general Swedish population. The 256 subjects (61% men) had a mean age of 45 ± 12 years at the inclusion. Liver biopsies were blindly scored for NAFLD and nonalcoholic steatohepatitis (NASH). Causes of death were ascertained from the national Swedish Cause of Death Registry. Fatty liver was detected in 143 of the 256 subjects, including 25 (10%) with alcoholic fatty liver disease and 118 (46%) exhibiting NAFLD. Of those, 51 (20%) were classified as NASH and 67 (26%) as nonalcoholic bland steatosis. Cirrhosis was present in 9% at inclusion. During the follow‐up period, 113 (44%) of the total population and 47 (40%) of the 118 subjects diagnosed with NAFLD died. Of the 113 deaths, 37 were of cardiovascular disease and 16 of liver diseases. Compared with the total Swedish population, adjusted for sex, age, and calendar period, subjects with NAFLD exhibited a 69% increased mortality (standardized mortality ratio [SMR] = 1.69; 95% confidence interval [CI], 1.24–2.25); subjects with bland steatosis, a 55% increase (SMR, 1.55; 95% CI, 0.98–2.32; P = 0.062); and subjects with NASH, 86% (SMR, 1.86; 95% CI, 1.19–2.76; P = 0.007). Conclusion: Patients with NASH are at increased risk of death compared with the general population. Liver disease is the third most common cause of death among patients with NAFLD. (HEPATOLOGY 2009.)